PERBEDAAN GANGGUAN PENDENGARAN AKIBAT BISING ANTARA OPERATOR CCR PLTU DENGAN PLTGUDI PT PJB UP GRESIK - Irvan Prayogo; Noeroel Widajati (The Indonesian Journal of Occupational Safety and Health, 2015)
ABSTRACTThe role of central control room (CCR) operator in Steam Power Plant (PLTU) or Gas and Steam Power Plant (PLTGU) of a work environment has high noise intensity with range (62.2– 99.8 dBA). Noise resulting from the process of production of electrical energy by machinery such as power generation unit boiler/HRSG, turbine, generator, condenser and other supporting equipment can cause Noise Induced Hearing Loss (NIHL). Study with cross-sectional design aims to analyze the difference in Noise Induced Hearing Loss between shift operator CCR PLTU and PLTGU PT PJB UP Gresik. Research on samples taken with the technique of simple random sampling with the majority of respondents were ≥ 40 years old, have a working periode ≥ 4 years, have a work area with a level of intensity noise > 85 dBA, long exposure noise ≤ 1 hour and good level of compliance of the use of ear protection in both of units. There was a difference of NIHL shift operator CCR PLTU and PLTGU. The number ofoperator who have experienced hearing loss due to noise on the shift operator CCR PLTU greater than PLTGU. Shift operator CCR PLTU and PLTGU are advised to obey and comply with safe working hours in areas with particular noise intensity has been set and the use of ear protection with right, also have to perform regular an audiometry exam tests so that the function of hearing of shift operator CCR could in monitor continuously.Keywords: central control room operator, power plant, noise induced hearing loss